2018
DOI: 10.1002/cssc.201801171
|View full text |Cite
|
Sign up to set email alerts
|

Acquiring High‐Performance and Stable Mixed‐Dimensional Perovskite Solar Cells by Using a Transition‐Metal‐Substituted Pb Precursor

Abstract: In recent years, as the most promising photovoltaic technology, lead halide perovskite solar cells (PSCs) have become a research hotspot owing to their super-high power conversion efficiency (PCE) and simple preparation method. However, the toxicity of lead and instability under high humidity and temperature greatly affects their further development. In this study, we investigated three kinds of non-toxic transition metal cations (Zn , Mn , and Ni ) at 3 % to partially substitute lead cations and form mixed-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…[57a] This was due to the low carrier mobility on the vertical direction caused by these insulating large organic cation layer supposedly parallel to the electrodes . Dai and co‐workers fabricated three MD perovskites by nontoxic transition metal cations (Zn 2 + , Mn 2 + , and Ni 2 + ) at 3% to partially replace lead cations in MAPbI 3 . The MD devices could, respectively, retain 81%, 80%, and 74% of their original PCE values under about 50% RH for 800 h. The PCE of MD perovskite devices maintained 84%, 85%, and 76% of their starting values at 60 °C for 100 h .…”
Section: Instability Of Phtotoactive Layer Of Pscsmentioning
confidence: 99%
See 1 more Smart Citation
“…[57a] This was due to the low carrier mobility on the vertical direction caused by these insulating large organic cation layer supposedly parallel to the electrodes . Dai and co‐workers fabricated three MD perovskites by nontoxic transition metal cations (Zn 2 + , Mn 2 + , and Ni 2 + ) at 3% to partially replace lead cations in MAPbI 3 . The MD devices could, respectively, retain 81%, 80%, and 74% of their original PCE values under about 50% RH for 800 h. The PCE of MD perovskite devices maintained 84%, 85%, and 76% of their starting values at 60 °C for 100 h .…”
Section: Instability Of Phtotoactive Layer Of Pscsmentioning
confidence: 99%
“…Dai and co‐workers fabricated three MD perovskites by nontoxic transition metal cations (Zn 2 + , Mn 2 + , and Ni 2 + ) at 3% to partially replace lead cations in MAPbI 3 . The MD devices could, respectively, retain 81%, 80%, and 74% of their original PCE values under about 50% RH for 800 h. The PCE of MD perovskite devices maintained 84%, 85%, and 76% of their starting values at 60 °C for 100 h . Leyden et al demonstrated that solar cells fabricated with FAPbI 3 as active layer had better thermal stability than those of MAPbI 3 .…”
Section: Instability Of Phtotoactive Layer Of Pscsmentioning
confidence: 99%
“…Power conversion efficiencies up to 20.06% [23] (with 1% of Zn(II) content) and enhancement factors of 1.07 to 1.33 (when comparing undoped and doped devices) are the trend. A PCE of 18.2% was reported by using 3% of ZnCl 2 in 2017 [11] and 18.35% in 2018 [14] with 3% ZnI 2 . A similar value (PCE = 18.25%) was found for 5% Zn(II) [15].…”
Section: Optical Properties Band Bending and Device Improvementmentioning
confidence: 95%
“…This finding is a second strong indication that Zn dopants are incorporated in the perovskite lattice. Dai et al came forward with a thorough work [14] on the doping of Pb perovskite with 3% of the transition metals Zn 2+ , Mn 2+ and Ni 2+ . The resulting materials were mixed dimensional perovskite films (MA(Pb:M)I 3 ) with a higher stability and in the case of the Zn 2+ (from ZnI 2 ), a superior photovoltaic performance of 18.35% (PCE, power conversion efficiency) (a 30% increase relative to undoped devices).…”
Section: Doping Of Perovskites With Zinc(ii)mentioning
confidence: 99%
See 1 more Smart Citation